The Leopard [videorecording (DVD)] - Visconti, Luchino, 1906-1976; Lancaster, Burt, 1913-1994; Delon, Alain, 1935-; Cardinale, Claudia, 1939-; Tomasi di Lampedusa, Giuseppe, 1896-1957 (Criterion collection, 2004)
Recounting the years of Italy's Risorgimento-when the aristocracy lost its grip and the middle classes rose and formed a democratic Italy. Contains the original Italian version with optional subtitles, the English-language version and special features.